2017
DOI: 10.7812/tpp/16-003
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of Volunteer Service at Safety-Net Clinics

Abstract: Background: Volunteer physicians are crucial for the operation of safety-net clinics, which provide medical care for uninsured and underinsured populations. Thus, identifying ways to maximize the number of physicians volunteering at such clinics is an important goal.Objective: To investigate the perceptions, motivations, functions, and barriers associated with physician volunteering in four safety-net clinics in San Bernardino County, Southern California, a location of great medical need with many barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Physicians generally have positive experiences with volunteering at community or safety net clinics, and the ability to focus more on patients, avoid organizational problems such as electronic medical records and regulations, and have more control over hours. These have been shown to improve well-being and protect against feelings of burnout ( 5 , 22 ). The main difficulty for physicians who wish to volunteer is the lack of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians generally have positive experiences with volunteering at community or safety net clinics, and the ability to focus more on patients, avoid organizational problems such as electronic medical records and regulations, and have more control over hours. These have been shown to improve well-being and protect against feelings of burnout ( 5 , 22 ). The main difficulty for physicians who wish to volunteer is the lack of time.…”
Section: Discussionmentioning
confidence: 99%
“…These include massage therapies, stress consultations and management classes which teach breathing, visualization, affirmations and mindfulness, yoga classes, aerobics classes, acupuncture, sportsmetrics, lifestyle coaches and nutrition consults. Volunteering has been associated with improved mental and physical health, an “escape hatch” from regular constrains of physician work, and may serve as an inoculation against trainee and physician burnout ( 5 ). We sought to investigate the impact of Hurricane Harvey on new trainees at our institute, and correlate volunteerism with measures of burnout and resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Participating in humanitarian efforts may increase provider satisfaction and decrease burnout by increasing psychological wellness via enhanced morale, social connections, and altruism [ 33 ]. Physician volunteers are most commonly motivated by humanitarian and prosocial desires [ 36 ], although a formal survey on volunteer satisfaction in our setting would be needed to investigate this further. Our ongoing involvement with Hope@UMHS illustrates the sustainability of volunteerism within our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Nonprofit leaders that fail to initiate positive impressions of the organization reduce volunteer reten-tion (Carvalho & Sampaio, 2017). Individuals that feel part of the organization and trust the leaders remain loyal (McGeehan, Takehara, & Daroszewski, 2017). Rowe and Alexander (2015) suggested environments of transparency and openness increase trust in organizations.…”
Section: Trust and Transparencymentioning
confidence: 99%
“…Leaders who meet the needs of volunteers increase donated hours and accomplish the organization's needs (Scherer et al, 2016). Additionally, McGeehan et al (2017) provided information that suggested physicians may volunteer their services through marketing focused on volunteering during a discretionary time to eliminate burnout. Herd, Adams-Pope, Bowers, and Sims (2016) suggested healthcare organizations that implemented strategies focused on programs to support future leaders through education and ongoing development created value to address change.…”
Section: The Relationship Between Engagement and Sustainabilitymentioning
confidence: 99%